Philodendron subg. Philodendron (Araceae) from the State of Rio de Janeiro: diversity and taxonomy - Mattos, Juliana Ribeiro De; Coelho, Marcus A. Nadruz; Baumgratz, José Fernando A. (Phytotaxa, 2026)
The neotropical genus Philodendron is widely distributed in Brazil, with a presence in almost all States, except for the State of Mato Grosso do Sul. Compared to other states in the Southeast region, the State of Rio de Janeiro is smaller in area, but it has the most preserved Atlantic Forest. The species of the subgenus Philodendron are characterized by being hemiepiphytic herbs with a spadix inflorescence implied by a spathe, with the intermediate sterile zone smaller than the male fertile zone. The present study focuses on the morphology and taxonomy of the subgenus Philodendron in the State of Rio de Janeiro, providing an identification key, species descriptions, geographic distribution data, phenology, comments, and conservation status. Twenty-one species were recognized within the state and classified into four different sections: Baursia, Macrobelium, Philodendron, and Schizophyllum. Seven of these species were assessed as belonging to some category of threat, and a new species was described. Two species, Philodendron acutatum, and Philodendron curvilobum, were excluded from the flora as they were found not to occur in the state. Philodendron inops was considered endemic to the municipality of Petrópolis, while Philodendron imbe was regarded as a doubtful species, as it was not found in its natural habitat.